Avaliação do comportamento da temperatura da superfície terrestre do município de Cariacica (ES) em 1985 e 2013 - Jesus, Rafael Justino de (2016)
The objective of this master's dissertation is to evaluate the behavior of the Earth's surface temperature and identify potential s Surface Heat and Freshness Island of the Municipality of Cariacica - ES, and correlating those behaviors facing the transformations in the use and Earth cover in 1985 and 2013.The assessments were funded by the proposed methodology linked to the geo-technologies - especially Remote Sensing, through the images of the satellites Landsat-5 and Landsat-8. The Surface Temperature was obtained through the coefficients of the calibration described by Chander et. al (2009), USGS (2015) and the sequence methodological used by Collischonn (1998) and Silva (2014) that considered the emissivity factor in obtaining. The mapping of use and land cover was carried out through the classifier and the automatic hybrid MAXVER, and the classes were guided by the Technical ManualUse and Land-Cover of the IBGE, such as: Rock Outcropping, Vegetation Cover, Water Body, Urban, Pasture/Exposed Soil, and Shadow. It should be noted that the technical procedures have been processed by the software ArcMap 10.1 – linked to the Laboratory of Cartography and Geographical and geo-technologies at the Federal University of the Espirito Santo. The results showed an association between the intervals of warmer temperature with the classes Urban and Pasture/Exposed Soil, mainly through the densification of the urban area witnessed in 2013; the areas of more moderate temperatures were significantly associated with the classes in the Vegetation Cover and Water Body. Spatially, the urban area was the one that registered the highest temperatures and the rural area the more mild ones, however, the cores of the heat of the surface have been identified on both the surfaces and distributed without a spatial organization. In this sense, consider-if the information coming from Remote Sensing techniques as important tools to support and complement the analysis of urban climate, in addition, can be used for urban planning so as to guide potential zoning front of the behavior found earlier in a given space.